Cerebral metabolism, anatomy, and cognition in monozygotic twins discordant for dementia of the Alzheimer type. Issue 3 (March 1987) - Luxenberg, J S; May, C; Haxby, J V; Grady, C; Moore, A; Berg, G; White, B J; Robinette, D; Rapoport, S I
Abstract : One pair of monozygotic twins discordant for dementia of the Alzheimer type (DAT) was studied using neuropsychological testing, quantitative x-ray computed tomography (QCT) and magnetic resonance imaging (MRI) of the brain. Cerebral glucose metabolism was measured using positron emission tomography (PET) and 2-[18-F]fluoro-2-deoxy-D-glucose (FDG). The affected twin had a seven year history of progressive cognitive impairment and was severely demented. Neuropsychological testing of the affected twin demonstrated marked deficits in all areas of cognitive function. The asymptomatic twin showed some impairment on tests of perceptual organisation and delayed recall. The affected twin had loss of gray matter and ventricular enlargement on QCT and MRI compared with healthy controls (p less than 0.05). He also had frontal and parietal lobe hypometabolism and increased asymmetry of metabolism on PET compared to both his twin and healthy age-matched controls (p less than 0.05). PET, QCT, and MRI distinguished changes in the twin with DAT compared with his brother and healthy controls. Although the subtle neuropsychological abnormalities of the asymptomatic twin may be signs of early DAT, they were not accompanied by any changes in regional cerebral metabolism or brain structure.